PENGEMBANGAN E-MODUL STATISTIK PENELITIAN PENDIDIKAN SEBAGAI INOVASI PEMBELAJARAN DI ERA MEA - Fitriyanti; Hudaidah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
One of the capabilities that must be mastered in the era of the Asean Economic Community (AEC) is the ability in the field of information and communication technology. Information technology (ICT) is a tool that can be used dalamkegiatan learning. For that perform the Development of E Module Statistics Education Research. This research aims to develop a valid E Module, practical and have a potential effect on student learning outcomes. Stages of development includes the planning, production and evaluation. Gathering data using questionnaires, tests, documentation and data analysis using quantitative descriptive. Based on the results of this study concluded that the E-Module developed declared valid, practical and have a potential effect as well as the positive feedback of students in its application. E-Module weaknesses in this study are: some students are poorly understood sentences. It is suggested that in future studies to use the phrase that corresponds to the student's understanding.